2021
DOI: 10.3390/app112210541
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Evaluation of Force–Velocity Variables in Flywheel Squats: Validity and Reliability of Force Plates, a Linear Encoder Sensor, and a Rotary Encoder Sensor

Abstract: Research into flywheel (FW) resistance training and force–velocity–power (F–v–P) profiling has recently gained attention. Ground reaction force (GRF) and velocity (v) during FW squats can be predicted from shaft rotational data. Our study aimed to compare the inter-set reliability of GRF, v, and F–v–P relationship output variables calculated from force plates and linear encoder (presumed gold-standard) and rotary encoder data. Fifty participants performed two sets of FW squats at four inertias. Peak and mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…These results opened some questions regarding the direct comparison of the F-v profiles due to the difference in the tempo of the motor task execution. Future studies should be focusing on the determination of the optimal methodology for comparing the F-v outcomes between CMJ and FW squats ( Spudić et al, 2021a ). Moreover, it was shown that previous experience in the use of FW devices influences mechanical squat performance ( Galiano et al, 2021 ; de Keijzer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results opened some questions regarding the direct comparison of the F-v profiles due to the difference in the tempo of the motor task execution. Future studies should be focusing on the determination of the optimal methodology for comparing the F-v outcomes between CMJ and FW squats ( Spudić et al, 2021a ). Moreover, it was shown that previous experience in the use of FW devices influences mechanical squat performance ( Galiano et al, 2021 ; de Keijzer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…By means of an FW device, the method allows for significantly increased eccentric force demands compared to traditional resistance exercises ( Norrbrand et al, 2011 ; Smajla et al, 2021b ). Further, when performing an FW squat with delaying the braking action in the first third of the eccentric phase, greater eccentric than concentric peak force production can be achieved, which is known as an eccentric overload ( Tesch et al, 2017 ; Spudić et al, 2020 ; Spudić et al, 2021a ). It was previously found that, despite the full voluntary effort, neuromuscular activation of the quadriceps femoris muscle appears inhibited during slow and fast eccentric contractions ( Aagaard et al, 2000 ) due to tension-limiting mechanism specific to eccentric action ( Amiridis et al, 1996 ; Alcazar et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations